Pharmacist characteristics, medication use perceptions, and professional satisfaction: a first national survey in the state of Qatar - Maguy Saffouh El Hajj; Nadir Kheir; Manal Zaidan; et al (Dove Medical Press, 2011)
Maguy Saffouh El Hajj1, Nadir Kheir1, Manal Zaidan2, Peter J Jewesson11College of Pharmacy, Qatar University, Doha, Qatar; 2Pharmacy Department, Al Amal Cancer Centre, Doha, QatarPurpose: To characterize the professional demographics, opinions about the medication use process, perceived public satisfaction with pharmacy services, and professional satisfaction of pharmacists practicing in the state of Qatar.Materials and methods: The study was designed as a hypothesis-generating, online, anonymous, opinion survey of practicing pharmacists in Qatar.Results: Two hundred and sixty-four survey accesses were recorded during the 6-week study period, and 250 surveys containing responses to one or more questions were included in the analysis. Eighty-four percent of respondents reported graduating at least 5 years prior to the survey, and 86% held a baccalaureate degree in pharmacy as their highest degree. The most common source of the highest degree was one of five countries (Egypt, Jordan, India, Sudan, or Pakistan). Forty-five percent of respondents were working in a hospital setting, and 33% were in a community pharmacy. The lowest incidence of agreement across the 10 drug procurement and distribution process statements was observed for the adequacy of medication supplies statements (33% of all respondents). The highest incidence of agreement across the eight medication use process statements was for the statement pertaining to infrequent dispensing errors (68%), and the lowest incidence of agreement was observed for the statement pertaining to the adequacy of patient monitoring (30%). The pharmacist was chosen as the best candidate to resolve perceived unmet medication needs for four of eight statements, whereas physicians were most frequently chosen for three of the four remaining statements. Respondents' perceptions regarding patient satisfaction with the different elements of the medication use process revealed that the lowest incidence of agreement pertained to patients' satisfaction with the waiting time required to obtain their medications (35%). Forty percent of all respondents rated themselves as professionally dissatisfied. Improvements to their professional role, greater opportunities for professional development, and enhancements in human resource-related conditions were identified as potential remedies to this situation.Conclusion: This study represents the first known attempt to formally solicit the opinions of pharmacists in Qatar. The study results have provided valuable information regarding the demographic characteristics, pharmacist perceptions about the medication use process, and professional satisfaction of practicing pharmacists in the country. This information is being utilized to guide workforce planning, to help identify potential shortcomings in the health care system, and to better understand continuing education and professional satisfaction needs of Qatar's pharmacy practitioners. We encourage other countries to conduct similar surveys in order to better understand the characteristics, perceptions, and needs of their health care workers.Keywords: pharmacist, characteristics, medication use, perceptions, professional satisfaction